2017
DOI: 10.1016/j.jmii.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of anti-influenza drugs, intravenous peramivir against influenza virus infection in elderly patients with underlying disease

Abstract: We retrospectively analyzed data of 38 elderly patients, each with an underlying disease, to evaluate peramivir safety and efficacy. Six patients (15.8%) experienced adverse events, all tolerated. Median time from administration until the return to normal temperatures was 31.5 h (95% CI: 22.4-40.6). Results confirm intravenous peramivir's usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Underlining the significant resource consumption in elderly and comorbid patient groups, a retrospective peramivir study between 2012 to 2015 followed elderly inpatients (≥65 years) with influenza and existing comorbidities. Mean length of hospitalization was 14.0 days, with a range from 3‐155 days 52 …”
Section: Resultsmentioning
confidence: 99%
“…Underlining the significant resource consumption in elderly and comorbid patient groups, a retrospective peramivir study between 2012 to 2015 followed elderly inpatients (≥65 years) with influenza and existing comorbidities. Mean length of hospitalization was 14.0 days, with a range from 3‐155 days 52 …”
Section: Resultsmentioning
confidence: 99%
“…features have also been conducted, 14,[18][19][20][21][22] peramivir 300 mg single dose or 600 mg repeat dose as an effective antiviral option in patients with chronic respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous head‐to‐head trials of NAIs have focused on the general patient population receiving treatment for acute uncomplicated seasonal influenza 7,8,16,17 . Studies of patients with high‐risk features have also been conducted, 14,18‐22 including with peramivir 300 or 600 mg/d administered for 1‐5 days (mostly 1‐2 days) as needed 14 . This latter trial included patients with diabetes and chronic respiratory diseases and showed a shorter median duration of influenza for patients who received peramivir 600 mg/d compared with 300 mg/d 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Current anti-influenza virus drugs include amantadine, rimantadine, oseltamivir, zanamivir and paramivir, which target the life cycle of a virus (2,3). However, worldwide resistance to these drugs due to prolonged usage and the resulting immuno-compromised status already exists (4,5).…”
Section: Introductionmentioning
confidence: 99%